Chapter 2. The Texts: Writing and Literature in Kievan Rus’ and Muscovy - Nesset, Tore (Septentrio Educational, 2015)
In the previous chapter, we explored the history of medieval Russia. We now turn to an important characteristic of this society – the emergence of writing and literature. Needless to say, medieval texts are interesting in and of themselves, but the texts are of particular interest to us as historical linguists, since they represent a major source of data. This chapter provides you with important background knowledge about writing, alphabets, texts and literature. Questions we will consider include: How did writing come to Kievan Rus’? Which alphabets were used? In what language were the texts written? What was the standard language in Kievan Rus’? What kinds of texts have come down to us? Although this chapter is by no means a detailed history of medieval literature, you will learn about some important literary genres and key texts. Finally, this chapter gives you an opportunity to reflect on the differences between the medieval and modern concepts of literature. Download the video to learn more.